Quality of life in Women with Adverse Pregnancy Outcome in Karad (Indian Journal of Public Health Research & Development, 2020)
Pregnancy is a period from conception to birth. During this period several physical and emotional changesoccurs in women. Women should be physically and more over mentally prepared to have a baby in herwomb. Miscarriage is spontaneous loss of the fetus before 20 weeks of gestation. The rate of miscarriageincreases with a maternal age of less than 18years or an age of 35 years or more, an increasing number ofprevious miscarriage, and increasing parity. In rural population women are forced to marry at an early age.Objective: To study the quality of life on SF-36 questionnaire of women having adverse pregnancy outcomes.Materials and Methodology: The study was conducted in krishna institute of medical sciences ‘deemedto be’ university Karad. Subjects were selected according to inclusion and exclusion criteria. The subjectsunderwent test using quality of life questionnaire- SF36. Conclusion: The present study provided evidence to support the decline in quality of life of women withadverse pregnancy outcome.
Keywords: adverse pregnancy, miscarriage, quality of life, SF-36